The ‘Fugu-blouse’ controversy: Colonial perceptions and sartorial decolonisation in Ghana-Zambia relations - Nyamawero Navei (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2026)
Dress politics remains a crucial arena where colonial legacies, national identity, and diplomatic representation intersect. Yet how indigenous Ghanaian presidential attire is perceived within intra-African encounters is underexplored. This qualitative case study examines the February 2026 Ghana–Zambia 'fugu-blouse' controversy, in which Zambian social media users mislabelled President John Dramani Mahama's indigenous Ghanaian smock a 'blouse.' The resulting Ghanaian rebuttals and the subsequent Fugu Wednesday policy constitute a decolonial intervention. An integrated thematic and critical discourse analysis of 30 heterogeneous, purposively sampled data sources reveals that, among the sampled Zambian comments, misrecognition exemplifies enduring colonial epistemologies within intra-African encounters. The Ghanaian counter-discourses, however, fostered awareness, generated apologies from some Zambians, and reframed the smock as a symbol of nationalism, historical resistance, and cultural pride. The Fugu Wednesday policy emerged as a strategic state-led intervention for sartorial decolonisation and promotion of indigenous dress. Nevertheless, critical policy analysis reveals significant structural lapses. The policy directive lacks a dedicated funding strategy, implementation guidelines, monitoring mechanisms, and enforcement provisions, making compliance largely voluntary and thereby risking tokenism. Surging demand has also exposed supply constraints among smock weavers, yet the policy provides no explicit capacity-building support. The study concludes that the Zambian–Ghanaian ‘fugu–blouse’ controversy and the Fugu Wednesday policy response have collectively resignified the Ghanaian fugu as a national dress identity. This study advances postcolonial literature by identifying intra-African sartorial misrecognition as a neglected dimension of coloniality, showing how colonial logics shape African perceptions and why cultural literacy is essential for Pan-Africanism.